2020
DOI: 10.21203/rs.3.rs-62909/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omics Analysis at Serum Proteomic and Metabolomic Levels Reveals Mechanisms of Moxibustion for a Mouse Model of Ankylosing Spondylitis

Abstract: Background: Moxibustion is widely used in ameliorating symptoms of ankylosing spondylitis (AS). The aim of this study was to identify the potential molecular profiles of moxibustion on relieving AS mice through incorporating ultra-high-performance liquid chromatography quadrupole-time of flight mass spectrometry (UHPLC-Q-TOF/MS) based metabolomics approach and data independent acquisition-mass spectrometry (DIA-MS) based proteomic. Methods: In this research, mice with proteoglycan-induced spondylitis (PGISp) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…37 At present, many original pieces of research have explored the bone metabolism regulation mechanism of moxibustion intervention in AS, which are summarized below. Xu et al 38 revealed that moxibustion at acupoints of Shenshu (BL 23), Zusanli (ST36), and Mingmen (GV4) of AS mice could effectively inhibit the overexpression of ALP and OCN, reduce the new bone formation, and improve the mobility of the spine in AS mice. Lin and Wu 39 explored the effect of medicineseparated moxibustion on the pain and bone metabolism of AS.…”
Section: Bone Metabolism Regulation Mechanism Of Moxibustion In Ankyl...mentioning
confidence: 99%
See 1 more Smart Citation
“…37 At present, many original pieces of research have explored the bone metabolism regulation mechanism of moxibustion intervention in AS, which are summarized below. Xu et al 38 revealed that moxibustion at acupoints of Shenshu (BL 23), Zusanli (ST36), and Mingmen (GV4) of AS mice could effectively inhibit the overexpression of ALP and OCN, reduce the new bone formation, and improve the mobility of the spine in AS mice. Lin and Wu 39 explored the effect of medicineseparated moxibustion on the pain and bone metabolism of AS.…”
Section: Bone Metabolism Regulation Mechanism Of Moxibustion In Ankyl...mentioning
confidence: 99%
“…The results showed that moxibustion could achieve the balance of intestinal flora by down-regulating the number of sulfate-reducing bacteria and Bacteroides fragilis in intestinal microorganisms. Xu et al 38 found that moxibustion could reduce the permeability of the intestinal tract and improve the mechanical barrier function of colon by down-regulating the L-phenylalanine of intestinal flora and up-regulating the expression of short-chain fatty acid and intestinal mucosal synthetic protein L-threonine. Moreover, moxibustion could prohibit the inflammatory signaling pathway, up-regulate the protein expression of Foxp3 and IL-10, and finally improve the intestinal defense against inflammation.…”
Section: Intestinal Flora Regulation Mechanism Of Moxibustion In Anky...mentioning
confidence: 99%